Detailed study on the effect of nano-particle size on emission characteristics of diesel engine. (17th September 2019) - Rangabashiam, Devaraj; Logesh, K.; Yashvanth, U.; Subbiah, Ganesan; D, Christopher Selvam
Abstract: This work examines the effect of particle size of silicon oxide (SiO2 ) nanoparticle on the emissions characteristics of four-stroke, single cylinder water-cooled diesel engine fueled with neat diesel (D100). Silicon oxide as an additive in various particle-size of 10 nm and 20 nm is included to D100 and termed as D100SiO2 10 and D100SiO2 20. The experimental result proved that the CO and HC emissions are 3.3% and 3.7% lower for D100SiO2 10 than D100 at 3.5 bar BMEP. SiO2 nanoparticle further reduces CO and HC emissions by 3.2% and 2.6% correspondingly for D100SiO2 20 than D100. The degree of NOx emission in D100 is 4.6% higher at 3.5 bar BMEP. When compared to D100, tailpipe NOx emission was found to be 1.7% and 2.6% lower when fueled with D100SiO2 10 and D100SiO2 20. In addition, the tailpipe smoke emission was found to be 0.7% lower when fueled with D100.